Performance of the most recent MCP-PMTs - Böhm, Merlin; Krauss, S.; Lehmann, Albert; Miehling, Daniel; Pfaffinger, Markus; Stelter, Samuel; Uhlig, Fred; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; et al. (Journal of Instrumentation, 2020)
For the identification of charged and fast moving particles two DIRC (detection of internally reflected Cherenkov light) detectors are being built for the PANDA experiment. They will provide hadronic particle identification in the PANDA target spectrometer and require lifetime-enhanced MCP-PMTs as sensors. MCP-PMTs are the only viable option for this task because they work in high magnetic fields of > 1 Tesla, have low dark count rates and an excellent time resolution of < 120 ps RMS. The tubes being deployed in the experiment have to be tested to find out if they comply with these requirements. These tests are performed in a semi-automatic setup which allows to measure time resolution, dark count rate, afterpulse probability, crosstalk behaviour, quantum efficiency, and gain distribution. The measurements are done with a picosecond laser attached to a 3-axis stepper to scan the sensor surface. Measurements and results of close-to-final prototype tubes are presented here.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Cherenkov detectors; Photon detectors for UV; Photon detectors for UV; Visible and IR photons (vacuum); Visible and IR photons (vacuum) (photomultipliers HPDs others)